Information System Prototyping of Strawberry Maturity Stages using Arduino Uno and TCS3200 - Juliano, Ariagi; Hendrawan, Ade Hendri; Ritzkal, Ritzkal (Universitas Muhammadiyah Yogyakarta, 2020)
Strawberry is one of the commodities of subtropical fruits growing in Indonesia. It has a high economic value, attractive appeal in a red and fresh sweet fruit. The color of a strawberry shows its maturity stages, and the strawberry maturity stages affect postharvest quality. The research aimed to design and implement a tool to approve and apply the maturity stages of strawberries using Arduino Uno and display the information on the web. The method included needs analysis and analysis of work, and the design consisted of hardware design and network design. The testing consisted of TCS3200 sensor testing, LCD testing, servo motor testing, and WEB testing. The results of this study found that when the strawberry fruit was declared mature by the TCS3200 sensor as the color detection sensor, the LCD would display the texts, and the servo would open. The system on the WEB would display the total information of the sorted strawberries.